2020
DOI: 10.1161/atvbaha.120.314168
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-Function CREB3L3 Variants in Patients With Severe Hypertriglyceridemia

Abstract: Objective: Genetic determinants of severe hypertriglyceridemia include both common variants with small effects (assessed using polygenic risk scores) plus heterozygous and homozygous rare variants in canonical genes directly affecting triglyceride metabolism. Here, we broadened our scope to detect associations with rare loss-of-function variants in genes affecting noncanonical pathways, including those known to affect triglyceride metabolism indirectly. Approach an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Importantly, humans with heterozygous CREB3L3 loss-of-function or missense mutations exhibit hypertriglyceridemia (3,4). Furthermore, a recent study found that individuals with severe hypertriglyceridemia were 20 times more likely than controls to carry loss-of-function mutations in CREB3L3 (5). Because CREB3L3 loss-of-function mutations are rare, it is not yet known if such individuals exhibit an increased cardiovascular disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, humans with heterozygous CREB3L3 loss-of-function or missense mutations exhibit hypertriglyceridemia (3,4). Furthermore, a recent study found that individuals with severe hypertriglyceridemia were 20 times more likely than controls to carry loss-of-function mutations in CREB3L3 (5). Because CREB3L3 loss-of-function mutations are rare, it is not yet known if such individuals exhibit an increased cardiovascular disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…This group of disorders are the most frequent cause of the CS, occurring in about 1;600 of the population (3,7,9,10). They are thought to result from the clustering of multiple genetic variants that include both rare heterozygous variants of the LPL, APOC2, APOA5, APOB, GCKR, LMF1, and GPIHBP1 genes and more frequent variants with small effects in~40 genes.…”
Section: Polygenic Causes Of Hypertriglyceridemia-multifactorial Chylmentioning
confidence: 99%
“…They are thought to result from the clustering of multiple genetic variants that include both rare heterozygous variants of the LPL, APOC2, APOA5, APOB, GCKR, LMF1, and GPIHBP1 genes and more frequent variants with small effects in~40 genes. Recently, CREB3L3, the gene for the transcription factor cyclic AMP-responsive element-binding protein H (CREBH), which is induced by metabolic cues such as fasting and fatty acids and leads to increases in APOC2 and APOA5 and reduction in APOC3 production has been shown to be associated with MFCS (10). In most cases these genetic variants are thought to require an aggravating effect of one or more secondary conditions or medications that exacerbate the metabolic defect leading to saturation of clearance mechanisms to cause the CS.…”
Section: Polygenic Causes Of Hypertriglyceridemia-multifactorial Chylmentioning
confidence: 99%
See 1 more Smart Citation
“…Because there is a difference in lipid metabolism between rodents and human beings, the pathophysiological relevance of these findings needs to be confirmed in future clinical studies. Second, multiple nonsynonymous mutations in CREB3L3 that produce a hypomorphic or nonfunctional Creb3L3 protein were identified in patients with extreme hypertriglyceridemia 14,19 ; it remains to be analyzed how these mutations affect the antagonism of CREB3L3 by SREBP. Other important aspects that also remain to be characterized are the binding domains for the interaction of SREBP and CREB3L3, as well as other novel interacting partners of the CREB3L3-SREBP complex.…”
mentioning
confidence: 99%